Inquérito brasileiro de colangite esclerosante primária: características clínicas e desfechos de uma população altamente miscigenada - Mateus Jorge Nardelli (2023)
BACKGROUND: Primary sclerosing cholangitis (PSC) is associated with a broad phenotypic spectrum in different populations from diverse ethnic and racial backgrounds. This study aimed to describe the clinical characteristics and outcomes of PSC in a multicenter cohort of patients from Brazil. METHODS: Data from the Brazilian Cholestasis Study Group were retrospectively reviewed to assess demographic information and clinical characteristics of PSC, as well as the outcomes, such as transplantation-free survival. RESULTS: This cohort included 210 patients. After excluding 33 (15.7%) patients with PSC and overlap syndrome of autoimmune hepatitis, 177 (97 males, median age 33 [2142] years) with clear-cut PSC were eligible for this study. Most of the patients (n=139, 78.5%) were symptomatic, and 104 (58.7%) had advanced PSC at the time of diagnosis. Concurrent inflammatory bowel disease was observed in 78 (58.6%) of the investigated patients (n=133), and most of them had ulcerative colitis (n=61, 78.2%). The 1- and 5-year survival free of liver transplantation or death were 92.3±2.1% and 66.9±4.2%, respectively, and baseline advanced PSC, pruritus, and elevated bilirubin levels were independent risk factors for the composite adverse outcome. Females were significantly older and had lower bilirubin levels than males at baseline, but survival was not associated with sex. Approximately 12.4% (n=22) of patients with PSC died, and 32.8% (n=58) underwent liver transplantation at a median follow-up time of 5.3 and 3.2 years. CONCLUSION: Multiethnic Brazilian PSC patients exhibited a less pronounced male predominance and a lower frequency of inflammatory bowel disease than Caucasians. Adverse outcomes were more frequent, probably due to advanced disease at baseline.